(untitled) (Халықаралық қатынастар және халықаралық құқық сериясы, 2023)
In this study, I focus on the unique case of Türkiye where both Ukrainian refugees and Russian émigrés bond in two magnet cities Istanbul and Antalya. In order to bridge the gap between research, policy and practice, in this article, I offer an analytical tool to understand “new wave” of emigration from Russia by focusing on the case of Russian digital nomads in Türkiye. Neither a descriptive nor an explanatory study was previously carried out on Ukrainian refugees and Russian émigrés in Türkiye. Therefore, I constructed an exploratory study based on a qualitative approach combining policy analysis, ethnographic observations, primary data from semi-structured and in-depth interviews with, government officials, and international and inter-governmental organization representatives in Türkiye. Between European and Eurasian migration systems, Türkiye offers an original and understudied migratory environment hosting both Ukrainian refugees and Russian émigrés. The preliminary findings of this research designate new and emerging cases, structures, and relations beyond Europe since the Russian invasion and conceptualize Russian digital nomads, as the agents of the “new wave” of emigration from Russia alongside with the changing migration patterns on the spheres of Europe.